An Econometric Model of the Medicare System: Reply - Feldstein, Martin S. (Quarterly Journal of Economics, 1973)
Journal Article An Econometric Model of the Medicare System: Reply Get access Martin S. Feldstein Martin S. Feldstein Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 87, Issue 3, August 1973, Pages 490–494, https://doi.org/10.2307/1882018 Published: 01 August 1973